THE INFLUENCE OF ORGANIZATIONAL CLIMATE, TRANSFORMATIONAL LEADERSHIP, AND WORK MOTIVATION ON TEACHER JOB PERFORMANCE - Kartini Kartini; Bedjo Sujanto; Mukhneri Mukhtar (Program Studi S3 Ilmu Manajemen, 2017)
This research aimed at investigating the influence of organizational climate, transformational leadership, and work motivation on teacher job performance at Pondok Modern Tazakka, Batang - Central Java.The research using quantitative approach with survey method. Amount of the samples in this research are 55 teachers that selected randomly. The data were analyzed by using descriptive statistics and inferential statistic using path analysis. (1) organizational climate have positive direct effect on teacher performance with path coefficient (py1) = 0,257 and t-count 2,963> t-table 1,684; (2) transformational leadership have positive direct effect on teacher performance with path coefficient (py2) = 0,489 and t-count 5,164> t-table 1,684, (3) work motivation have positive direct effect to teacher performance with path coefficient (py3) = 0,261 and t count 2,42> t-table 1,684, (4) organizational climate have positive direct effect (p31) = 0.391 and t-count 3.990> t-table 1.684, and (5) transformational leadership have a direct positive effect on work motivation with path coefficient (p32) = 0.526 and t-count 5,376> t- table 1,684. The Conclusion is organizational climate, transformational leadership, and work motivation have a direct effect on teacher job performance. Organizational climate and transformational leadership also have a direct effect on teacher work motivation. Therefore to improve teacher job performance, organizational climate, transformational leadership, and work motivation must be considered to be improved.